(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The article explores how new technologies are revolutionizing foreign language learning, making education more accessible, engaging, and effective. It highlights the integration of tools such as mobile apps, virtual reality (VR), artificial intelligence (AI), and online platforms in language education. These technologies offer interactive and personalized learning experiences, facilitating real-time feedback, immersive environments, and global connectivity for practicing language skills. The paper also discusses the challenges of technological integration, including digital literacy and equitable access, and emphasizes the importance of balancing technology with traditional teaching methods.